Payment Social Charity from the Muslim Community in Jayapura with an Explanatory Research (UIN Sunan Kudus, 2022)
This paper aims to investigate why Muslim communities prefer to pay social charity to private non-profit institutions during natural and humanitarian disasters. This is quantitative research with an explanatory analysis method. The population in this study was the entire Muslim population of Jayapura City, Papua Province. Pre-observational research found that only 11% (22 respondents) of 200 respondents paid social charity to official government-owned institutions, while 89% (178 respondents) paid social charity to private non-profit institutions. Therefore, we obtained data using a questionnaire from 178 respondents who paid social charity to private non-profit organizations. The results show that three important variables can explain why people prefer to pay Islamic social finance to private non-profit institutions: channeling effectiveness, ease of access, and social influence. This study makes implications for private non-profit organizations on how to keep contributors' trust by paying attention to how donors' money is distributed, how accurately donations are distributed, and how the organization is perceived. The example set by private nonprofit organizations should be followed by government-owned private nonprofit organizations to improve their donor services.